2022
DOI: 10.3389/fpubh.2022.1074559
|View full text |Cite
|
Sign up to set email alerts
|

Self-medication in Chinese residents and the related factors of whether or not they would take suggestions from medical staff as an important consideration during self-medication

Abstract: ObjectiveTo investigate the status of Chinese residents' self-medication behavior and the important factors to consider when purchasing OTC drugs, and to explore the related factors of the possibility that Chinese residents take medical staff's suggestions as important factors to consider when purchasing OTC drugs.Study designA cross-sectional survey.MethodsA questionnaire was developed for exploring the sociodemographic characteristics of the respondents, their self-medication status, and important considerat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 83 publications
0
2
0
Order By: Relevance
“…Self-help, mutual aid, and some other spontaneous community measures have proven to be effective in dealing with COVID-19 [58]. Given the difficulty in obtaining timely prescriptions of antivirus drugs and factors such as availability and panic buying, ordinary publics used social media as a platform to search for and share/sell medications, perhaps without formal instructions from doctors [71]. Our results also showed that TCM formulae or proprietary Chinese medicines remained prominent in topics in all 3 models, especially in the whole data set (model 1) and in the later period (model 3).…”
Section: Topic Characteristics During China's Exit From the Zero-covi...mentioning
confidence: 99%
“…Self-help, mutual aid, and some other spontaneous community measures have proven to be effective in dealing with COVID-19 [58]. Given the difficulty in obtaining timely prescriptions of antivirus drugs and factors such as availability and panic buying, ordinary publics used social media as a platform to search for and share/sell medications, perhaps without formal instructions from doctors [71]. Our results also showed that TCM formulae or proprietary Chinese medicines remained prominent in topics in all 3 models, especially in the whole data set (model 1) and in the later period (model 3).…”
Section: Topic Characteristics During China's Exit From the Zero-covi...mentioning
confidence: 99%
“…According to a recent survey, antipyretic analgesics rank at the top of OTC drugs that have been purchased and utilized. Among respondents, 58.57% have purchased and used antipyretics (13). However, there is a lack of KAP assessments focused on Chinese fever patients.…”
Section: Introductionmentioning
confidence: 99%